10-9+1= 6+4+8= 6+5=

10-4+3= 3+7+6= 9+1=

10-5+2= 5+5+7= 8+5=

10-4+1= 2+8+4= 7+3=

10-8+2= 1+9+6= 8+4=

10-7+4= 4+6+8= 1+6=

10-5+3= 8+2+3= 4+9=

10-6+4= 9+1+8= 6+4=

10-8+5= 6+4+5= 9-6=

10-9+7= 9+1+3= 8-3=

我用了_______________分_______________秒,對_______________道,錯_______________道。

6+8= 6+4= 8+7=

3+9= 9-6= 7-4=

6-4= 9-7= 9+9=

2+7= 8-3= 2+4=

1+6= 8-2= 6+6=

0+9= 7-5= 5+9=

6-6= 4-3= 8-4=

9-2= 9-4= 4+9=

8-6= 9-5= 6+5=

7-3= 8-1= 3+7=

我用了_______________分_______________秒,對_______________道,錯_______________道。